The monk (1796): a hispanist's reading - Abigail Lee Six (Ilha do Desterro)
This article argues that the honour plays of seventeenth-centurySpain have been overlooked as precursors to the Gothic. ReadingLewis’s The Monk through this prism reveals that Spanishconcept of honour plays sheds light upon the characterization ofAmbrosio. Furthermore, the honour code gives rise to numerousareas of common ground with the Gothic, including the centralityof sexual secrets, imprisoned women, and a predilection forgore. Lewis’s opportunities for access to this Spanish corpus areconsidered and finally, it is posited that the post-eighteenthcenturyfigure of the Gothic villain who is troubled and complexmay be traceable, via The Monk, to the Spanish Golden Age.